Prognostic Value of GRACE Risk Scores in Patients With Non-ST-Elevation Myocardial Infarction With Non-obstructive Coronary Arteries - Yin, Guoqing; Abdu, Fuad A.; Liu, Lu; Xu, Siling; Xu, Bin; Luo, Yanru; Lv, Xian; Fan, Rui; Che, Wenliang (Frontiers in Cardiovascular Medicine, 2021)
Myocardial infarction with nonobstructive coronary arteries (MINOCA) is a special type of myocardial infarction (MI). The GRACE risk score is commonly used to predict major adverse cardiovascular events (MACE) in non-ST-elevation myocardial infarction patients, and the suitability of the GRACE risk score for prognostic stratification in patients with MINOCA remains uncertain. This study aimed to investigate whether the GRACE risk score is capable of predicting MACE in MINOCA patients with NSTE. We calculated the GRACE risk score for 340 consecutive MINOCA patients with NSTE. Patients were divided into a low-intermediate risk group (≤140, 48.8%) and a high risk group (>140, 51.2%) according to their GRACE risk scores. The clinical characteristics and outcomes of the patients were assessed. Patients in the high risk group tended to be older and to have more comorbidities. At the one-year follow-up, the rate of cardiac death in the high risk group was significantly higher than that in the low-intermediate-risk group (p=0.010). There was no significant difference in nonfatal MI, stroke, heart failure, or cardiovascular-related rehospitalization. The incidence of total MACE was significantly higher in patients with high GRACE risk scores than in patients with low GRACE risk scores (p=0.006). ROC curve analysis showed that the GRACE risk score has moderate value in predicting MACE in NSTE-MINOCA patients. The area under the ROC curve was 0.710 (95% CI 0.625 to 0.796, P<0.001). The GRACE risk score provides potentially valuable prognostic information on clinical outcome when applied to MINOCA patients with NSTE.